A173 EVALUATION OF LIVER FIBROSIS SCORES POST-HCV SVR IN PEOPLE WHO INJECT DRUGS. (1st March 2018) - Raycraft, T; Singh, A; Alimohammadi, A; Shahi, R; Kiani, G; Truong, D; Conway, B
Abstract: Background: In the developed world, people who inject drugs (PWID) constitute the majority of prevalent and incident Hepatitis C (HCV) infections. Treatment is often withheld due to concerns surrounding reduced efficacy related to poor adherence and a higher risk of re-infection after successful treatment. Current guidelines favour increasingly widespread access to highly effective direct-acting antiviral regimens within this population, with a view to curing HCV infection but also preventing HCV transmission. An additional rationale for treatment may be to prevent the liver-related morbidity and mortality increasingly prominent among PWID. Data on the impact of HCV cure on liver fibrosis scores among PWID have not yet been generated in a systematic way. Aims: The aim of this study is to assess the regression of fibrosis in people who inject drugs after achievement of HCV SVR. Methods: We performed a retrospective observational study utilizing records of PWID successfully treated for HCV infection at our centre. HCV-infected PWID with ongoing recreational drug use, having achieved and maintained a sustained virologic response (SVR) and engaged in long-term medical follow-up were included. Fasting transient elastography (TE) scores post-SVR were compared to pre-treatment values. If such scores were unavailable, APRI scores were considered. Results: A cohort of 57 subjects were included in this analysis. Of these, 45 (79%) actively injected drugs during treatment and 12 (21%) did so intermittently before and after HCV treatment. The median age was 53 (27–73) years, 47 (82%) were male, 52 (91%) were Caucasian, 42 (74%) were infected with HCV genotype 1, and 12 (21%) were genotype 3. In addition, 77% were HCV treatment-naïve and 10 (18%) were HIV co-infected, 9 (90%) of whom demonstrated complete virologic suppression (HIV viral load <40 copies/mL). The mean follow-up period was 472 (128–1247) days. Based on TE evaluations, the mean pre-treatment fibrosis scores of 11.9 (3–45) kPa (3–45) significantly decreased post-treatment to a mean of 9.6 (2–27) kPa (p=0.03). Mean APRI scores decreased from 0.91 to 0.40 (p=0.0001). Among 12 patients that initially suffered from cirrhosis (TE score >12.5 kPa), 11 (92%) had improved fibrosis scores after treatment, including 5 (42%) who decreased to a lower fibrosis category (F3 or less). Conclusions: This data set shows significant, rapid improvement in liver fibrosis among PWID successfully treated for HCV infection. In a population where liver-related morbidity and mortality is becoming a common clinical concern, this provides additional and strong rationale for the development of strategies to increase HCV treatment uptake. Funding Agencies: Canadian Network on Hepatitis C